Forced vibration of multidisc Shaft with rotating unbalance - Gautam, Bishwas; Luitel, Mahesh Chandra; Yadav, Pankaj (Journal of Innovations in Engineering Education, 2025)
Most of the modern day engineering systems use rotor dynamics for the transmission of power. The slightest imbalance in the rotor system can create a massive loss in the energy transfer and the system’s life. This study explores the dynamic behavior of multidisc shaft systems with rotating unbalance, a crucial area in mechanical engineering, by integrating analytical modeling, mathematical formulations, and finite element simulations using ANSYS. The shaft is modeled as a flexible Euler-Bernoulli beam, considering the gyroscopic effect, while the discs are considered rigid bodies with unbalance present in a disc. The equations of motion are derived using Extended Hamilton’s principle and solved to evaluate the system’s forced vibration response. For the system considered, which is rotating at the speed of 1500 RPM, in both transverse directions, the amplitude at the end of the shaft was found to be 41.495 micrometers, considering the unbalance of 0.0001kgm present at first disc positioned at one-third length of the shaft. The amplitude was 18.46 micrometers at the position of the second disc situated at two-thirds length of the shaft. The analytical results were considered with the numerical results of ANSYS, and variation in result was found to be less than 10 percent.